Binding Success and Failure: Evidence for the Spontaneous Integration of Perceptual Features and Object Evaluations - Hommel, Bernhard; Keizer, Andre (Frontiers in Psychology, 2012)
Humans represent perceptual events in a distributed, feature-specific fashion, which called for some sort of feature integration. It has been suggested that processing an event leads to the creation of a temporary binding of the corresponding feature codes—an object file. Here we show that object files do not only comprise of perceptual feature codes but also include codes that reflect evaluations of the perceptual event.